EcoJustice, Citizen Science and Youth Activism
XV, 460 p. 89 illus.
Keywords: This volume draws on the ecojustice, citizen science and youth activism literature base in science education and applies the ideas to situated tensions as they are either analyzed theoretically or praxiologically within science education pedagogy. It uses ecojustice to evaluate the holistic connections between cultural and natural systems, environmentalism, sustainability and Earth-friendly marketing trends, and introduces citizen science and youth activism as two of the pedagogical ways ecojustice philosophy can be enacted. It also comprises evidence-based practice with international service, community embedded curriculum, teacher preparation, citizen monitoring and community activism, student-scientist partnerships, socioscientific issues, and new avenues for educational research.